2010
DOI: 10.1002/aic.12487
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant‐free microdispersion process of gas in organic solvents in microfluidic devices

Abstract: in Wiley Online Library (wileyonlinelibrary.com).The scaling of bubble/slug formation in organic solvents at microscale without surfactant was initially investigated by using T-junction and symmetrically cross-shaped microfluidic devices. Four unique organic solvents and three dispersion methods were used, forming different flow patterns and dispersion size. The flow pattern of uniform slug flow was investigated. Both the gas-liquid flow and dispersion size, which ranged from 400 to 1400 lm in length and 270 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…Continuous gas phase flows downstream the main channel. The designations of squeezing, dripping, and laminar flows derive from previous gas-liquid two-phase microflow studies [31][32][33]. To show the similarity of two-phase microflow and three-phase microflow, a control group experiment without water feeding was also performed in the same microchannel device.…”
Section: Gas-phase Flow Behaviors At the Cross Junctionmentioning
confidence: 99%
See 1 more Smart Citation
“…Continuous gas phase flows downstream the main channel. The designations of squeezing, dripping, and laminar flows derive from previous gas-liquid two-phase microflow studies [31][32][33]. To show the similarity of two-phase microflow and three-phase microflow, a control group experiment without water feeding was also performed in the same microchannel device.…”
Section: Gas-phase Flow Behaviors At the Cross Junctionmentioning
confidence: 99%
“…For the dripping-ruptured bubbles, previous results indicated that the average bubble diameter is a function of channel size, phase ratio of gas phase to liquid phase, and capillary number of the continuous phase [31]. Eq.…”
Section: Size Laws Of Generated Bubbles and Dropletsmentioning
confidence: 99%
“…The dimensionless average bubble diameter has a linear relation with ð Q d Qc Þ 0:33 , which is close to the conclusion of previous work. 21 Using the model, we could calculate the bubble diameter in different conditions, the calculated data fit the experimental data well, as shown in Fig…”
Section: Bubble Generation In Single-pore Microdevicesmentioning
confidence: 82%
“…The micromixer is made of PEEK (polyether ether ketone) material with an inner diameter of 0.25 mm. The Y-shaped micromixer has been applied for the gas/liquid and liquid/liquid dispersion in previous literature. Water and Cl 2 gas flowed through the pipes immersed in Water Bath 1 to control the feeding temperature. A delay loop (polytetrafluoroethylene, PTFE) immersed in Water Bath 2 with an inner diameter of 1 mm and an external diameter of 1.6 mm was connected directly downstream to the second micromixer to control the reaction time.…”
Section: Methodsmentioning
confidence: 99%